Some Aspects Of The Succession Of Vegetation Of Desert Landscapes In The South Of The Aral Sea - Sevara Kochkarova, Polat Halmuratov, Svetlana Mambetullaeva (International Journal of Advanced Science and Technology, 2020)
The article considers a typological version of desert landscapes that combines the features of sandy and gypsum deserts. Halophilic vegetation is found both in continuous massifs and as separate spots on the territories of the Ustyurt plateau and the dried part of the bottom of the Aral Sea. Naturally, the described vegetation often comes into contact with other types of vegetation – tugai (forest), psammophilic, gypsophila, ephemeral, and in this connection, many transition halophytic communities are observed in nature. The vegetation of saline habitats is characterized by heterogeneity and spotting. A complex combination of plant communities is often observed even in a small area.